Livelihood intervention and mental well-being among women living with HIV in Delhi. Issue 8 (3rd August 2021) - Hosaka, Kalei R.J.; Kang, Ezer; Huff, James; Shaw, Sheeba; Duomai, Savita
ABSTRACT : Poverty-alleviation programmes aimed to improved mental well-being among persons living with HIV (PLWH) in low and middle income countries have underscored the importance of understanding how and why such programmes work. We present findings from a six-month ethnographic process evaluation of Kiran, an economic livelihood programme locally designed to improve mental well-being among women affected by HIV in Delhi, India. In addition to benefits of improved economic standing, we found that supportive relationships cultivated among participants ( n  = 9) and with providers ( n  = 3) provided respite from worry about their illness and reframed what was relationally and practically possible in the context of living with HIV. In acquiring marketable craft skills with peers, participants challenged internalized scripts of being socially devalued and regained agency about their abilities to contribute to their community and support their children's immediate and future needs. We found that the benefits of Kiran weighed less on the direct alleviation of mental distress and more on the instillation of hope for their children. Our findings exemplify the importance of re-visiting a priori theories that inform interventions for PLWH and highlight the methodological merits of ethnographic approaches that underscore how theory and intervention praxis are bidirectionally informed.